Islam and liberal citizenship: the search for an overlapping consensus - March, Andrew F. (Oxford University Press, 2009)
Andrew F. March demonstrates that there are very strong and authentically Islamic arguments for accepting the demands of citizenship in a liberal democracy, many of them found even in medieval works of Islamic jurisprudence